2022
DOI: 10.13187/ejced.2022.3.931
|View full text |Cite
|
Sign up to set email alerts
|

Academic Literacy as a Component of Complex Thinking in Higher Education: A Scoping Review

Abstract: The profound transformation within higher education institutions is increasingly evident. Then, it is considered that education must adapt to meet the needs of qualification and skills development in a 21st century with diverse challenges in problem solving. This is reflected in the role that academic literacy is increasingly taking as a strategy to innovate teaching among university students. The objective of this scoping review is to complete a characterization of complex thinking in both academic literacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…The results shown here, also show practical implications for the development of educational policies, as well as in the attention to the promotion of transversal competences in higher education students (García-González et al, 2019), specially, the mega competence of complex thinking Suárez-Brito et al, 2022).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results shown here, also show practical implications for the development of educational policies, as well as in the attention to the promotion of transversal competences in higher education students (García-González et al, 2019), specially, the mega competence of complex thinking Suárez-Brito et al, 2022).…”
Section: Discussionsupporting
confidence: 56%
“…All this, not only because it considers, epistemologically speaking, the foundations of "complex thought" to approach the sciences and their various fields in a multidisciplinary and systemic way; but also, because it has been concerned to show within the educational sciences that students must develop new capabilities, regardless of their training, to better meet the technological, environmental, social, political, and social challenges of the present (García, 2020;Vázquez-Parra, et al, 2022). Specifically, complex thinking understood as a mega competence, is a useful training tool for students and the educational community in general, to propose solutions to complex problems in an innovative way and with scientific bases (Suárez-Brito et al, 2022). As mentioned above, it is made up of the subcompetencies of critical, scientific, innovative, and systemic thinking (González-Pérez, Ramírez-Montoya et al, 2022), each of which presents its own characteristics, and are also conceived as part of the 21st Century Skills proposed by UNESCO (Fadel, 2008;UNESCO, 2017;UNESCO, 2022).…”
Section: Justificationmentioning
confidence: 99%
“…We must have a macro view, but without neglecting the micro instances that make up the whole social phenomenon; that is, the tree does not prevent us from seeing the forest, and the forest does not prevent us from examining the particularities of each tree. Bibliometric analyses of complexity identify challenges for education (Baena-Rojas et al, 2022;Ramírez-Montoya et al, 2022a;Suárez-Brito et al, 2022;Vázquez-Parra et al, 2022), where the habits of mind of systems thinking are fostered, with educational interventions that build and enhance the complex system with constituent subsystems (Kastens and Manduca, 2017). In particular, Morin (2019Morin ( , 2020 invites us to think of complexity as "interwoven, " where the parts are analyzed in the whole and the whole in correspondence with its parts.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review was carried out to identify previous studies related to the topic addressed in this research. Two scoping reviews were identified, one with the objective of exploring and describing methods and strategies to promote the development of academic literacy ( Klarare et al, 2022 ) and the other with the objective of completing a characterization of complex thinking in academic literacy and higher education ( Suarez-Brito et al, 2022 ). Five articles were found that addressed interventions, two of them focused on writing ( Olivier, 2019 ; Zashikhina, 2021 ), one aimed at academic writing in English ( Roux et al, 2018 ), one about a Center for Reading, Writing and Orality ( Soares Sito et al, 2019 ), and one research focusing on a program that was designed in such a way as to associate learning with the production and analysis of texts specific to the students’ field of study ( Urzúa-Martínez et al, 2021 ), and another article dealt with a cross-cutting program of academic literacy ( Pardo-Espejo and Villanueva-Roa, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon entering the university context, students encounter specialized knowledge and, therefore, need to develop specific strategies to engage in the different activities of text analysis and production required for learning in the context of higher education ( Carlino, 2013 ). Academic literacy in higher education becomes an essential element to promote, not only from reading but also from other much more complex competencies, all the human potential ( Suarez-Brito et al, 2022 ). Academic literacy is positioned as a competency worth investigating in the context of higher education.…”
Section: Introductionmentioning
confidence: 99%